The Usefulness of Functional Near-Infrared Spectroscopy for the Assessment of Post-Stroke Depression - Koyanagi, Masahiko; Yamada, Mai; Higashi, Toshio; Mitsunaga, Wataru; Moriuchi, Takefumi; Tsujihata, Mitsuhiro (Frontiers in Human Neuroscience, 2021)
Background: Post-stroke depression (PSD) is the most common mood disorder following stroke and is also the main factor that limits the recovery and rehabilitation of stroke patients. The prevalence of PSD is approximately 30%. Since there is no gold standard for the diagnosis and evaluation of PSD, it is important to raise awareness of PSD and to establish methods for its evaluation, early diagnosis, and treatment. In the field of psychiatry, functional near-infrared spectroscopy (fNIRS) has been used as a diagnostic tool for the measurement of oxygenated hemoglobin (oxy-Hb). This study aimed to assess whether fNIRS could be applied in the diagnosis and evaluation of PSD. Methods: We recruited 45 stroke patients who were admitted to our hospital between May 2015 and April 2019. The 17-item Hamilton Rating Scale for Depression (HAMD17), which is considered to be a useful screening and evaluation tool for PSD, was used for the assessment of post-stroke patients; moreover, oxy-Hb was measured in the prefrontal cortex. The subjects were divided into two groups: the depressed group (n=13) and the non-depressed groups (n=32). We evaluated the correlation between the oxy-Hb integral values and HAMD17 scores. Results: We investigated the relationship between the oxy-Hb integral values and HAMD17 total scores, and found a negative correlation between them (ρ=-0.331, P<0.005). There was a significant difference in the oxy-Hb integral values during the activation task period between the depressed and non-depressed groups (3.16±2.7 and 1.71±2.4, respectively; P = 0.040). The results indicated that the depressed group showed lower oxy-Hb integral values and lower activation in the frontal lobe in comparison to the non-depressed group patients. Conclusion: The present study highlights that the measurement of oxy-Hb using fNIRS, is a useful method for diagnosis of PSD in post-stroke patients.